Anti-CD20 as the B-Cell Targeting Agent in a Combined Therapy to Modulate Anti-Factor VIII Immune Responses in Hemophilia a Inhibitor Mice - Liu, Chao Lien; Ye, Peiqing; Lin, Jacqueline; Butts, Cherie L.; Miao, Carol H. (Frontiers in Immunology, 2014)
Neutralizing antibody formation against transgene products can represent a major complication following gene therapy with treatment of genetic diseases, such as hemophilia A. Although successful approaches have been developed to prevent the formation of anti-factor VIII (FVIII) antibodies, innovative strategies to overcome pre-existing anti-FVIII immune responses in FVIII-primed subjects are still lacking. Anti-FVIII neutralizing antibodies circulate for long periods in part due to persistence of memory B cells. Anti-CD20 targets a variety of B cells (pre-B cells to mature/memory cells); therefore, we investigated the impact of B cell depletion on anti-FVIII immune responses in hemophilia A mice using anti-CD20 combined with regulatory T (Treg) cell expansion using IL-2/IL-2mAb complexes plus rapamycin. We found that anti-CD20 alone can partially modulate anti-FVIII immune responses in both unprimed and FVIII-primed hemophilia A mice. Moreover, in mice treated with anti-CD20 + IL-2/IL-2mAb complexes + rapamycin + FVIII, anti-FVIII antibody titers were significantly reduced in comparison to mice treated with regimens targeting only B or T cells. In addition, titers remained low after a second challenge with FVIII plasmid . Treg cells and activation markers were transiently and significantly increased in the groups treated with IL-2/IL-2mAb complexes ; however,significant B cell depletion was obtained in anti-CD20-treated groups. Importantly, both FVIII-specific antibody-secreting cells and memory B cells were significantly reduced in mice treated with combination therapy. This study demonstrates that a combination regimen is highly promising as a treatment option for modulating anti-FVIII antibodies and facilitating induction of long-term tolerance to FVIII in hemophilia A mice.